The role of eukaryotic initiation factor 3 in plant translation regulation - Raabe, Karel; Honys, David; Michailidis, Christos (Plant physiology and biochemistry, 2019)
Regulation of translation represents a critical step in the regulation of gene expression. In plants, the translation regulation plays an important role at all stages of development and, during stress responses, functions as a fast and flexible tool which not only modulates the global translation rate but also controls the production of specific proteins. Regulation of translation is mostly focused on the initiation phase. There, one of essential initiation factors is the large multisubunit protein complex of eukaryotic translation initiation factor 3 (eIF3). In all eukaryotes, the general eIF3 function is to scaffold the formation of the translation initiation complex and to enhance the accuracy of scanning mechanism for start codon selection. Over the past decades, additional eIF3 functions were described as necessary for development in various eukaryotic organisms, including plants. The importance of the eIF3 complex lies not only at the global level of initiation event, but also in the precise translation regulation of specific transcripts. This review gathers the available information on functions of the plant eIF3 complex.
Keywords: rostliny; Plants; regulace genové exprese u rostlin; Codon, Initiator; Translation regulation; eukaryotický iniciační faktor 3; Translation; Eukaryotic Initiation Factor-3; Protein Biosynthesis; Upstream open reading frame (uORF); proteosyntéza; kodon iniciační; Gene Expression Regulation, Plant; Plant development